Respostas
respondido por:
0
Basta supor valores para x e substituir no lugar de f(x)
Por exemplo,
X=0 ---- F(X) = [0-2]+0 = -2 , então vai ser o ponto (0,-2)
X=1 ----- F(x) = [1-2]+1 = 0 , entao vai ser o ponto (1,0)
X=2 ---- F(X) = [2-2]+2 = 2 , então vai ser o ponto (2,2)
Por exemplo,
X=0 ---- F(X) = [0-2]+0 = -2 , então vai ser o ponto (0,-2)
X=1 ----- F(x) = [1-2]+1 = 0 , entao vai ser o ponto (1,0)
X=2 ---- F(X) = [2-2]+2 = 2 , então vai ser o ponto (2,2)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás